Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1439-0434.2009.01564.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Conventional Identification and Pathogenicity of Rhizoctonia solani Isolates from Tobacco (Nicotiana tabacum L.) in Samsun, Turkey

Abstract: A total of 101 fungal samples were isolated from tobacco (Nicotiana tabacum L.) plants in Samsun, Turkey and identified as Rhizoctonia solani. Of these samples, three were identified as belonging to Anastomosis Group (AG) -1-IB, 6 to AG-2-1, 25 to AG-4-HG-I and 67 to AG-4-HG-II, using ITS1-5.8S-ITS2 rDNA RFLP analysis, base sequence phylogenies and conventional characters, such as anastomosis reactions, morphology and thiamine requirement. For five isolates from both the AG-4-HG-I and AG-4-HG-II groups and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…In the pathogenicity tests, R. solani AG 2-1 and AG 4 HG-I isolates caused the highest severity rating, with the highest DSI for target spot and damping-off, respectively. These results support previous observations (Gurkanli et al 2009;Bacharis et al 2010). R. solani AG 4 HG-I has been reported to be more aggressive than AG 4 HG-II and AG 2-1, causing damping-off symptoms on tobacco seedlings (Gurkanli et al 2009;Bacharis et al 2010).…”
Section: Discussionsupporting
confidence: 96%
See 2 more Smart Citations
“…In the pathogenicity tests, R. solani AG 2-1 and AG 4 HG-I isolates caused the highest severity rating, with the highest DSI for target spot and damping-off, respectively. These results support previous observations (Gurkanli et al 2009;Bacharis et al 2010). R. solani AG 4 HG-I has been reported to be more aggressive than AG 4 HG-II and AG 2-1, causing damping-off symptoms on tobacco seedlings (Gurkanli et al 2009;Bacharis et al 2010).…”
Section: Discussionsupporting
confidence: 96%
“…The predominance of AG 4 HG-I and AG 2-1 isolates was also observed by Gurkanli et al (2009) andBacharis et al (2010) in tobacco seedlings showing symptoms of dampingoff in Turkey and Greece. In this study, isolates obtained from plants with damping-off symptoms were identified as AG 4 HG-III and AG 2-1.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In Turkey, however, there are no reports on the presence of BN Rhizoctonia and MN R . solani on perennial plants, but there are many reports on annual plants, including barley and wheat (Demirci, ), corn (Demirci & Kordali, ), johnsongrass (Demirci, Eken, & Zengin, ), legumes (Eken & Demirci, ), potato (Yanar, Yilmaz, Cesmeli, & Coskun, ), onion (Erper et al., ), bean (Erper et al., ), tabocco (Gurkanlı & Ozkoc, ; Gurkanlı, Ozkoc, & Gunduz, ), pepper (Tuncer & Eken, ), winter squash (Erper, Cebi Kilicoglu, Türkkan, & Onder, ). In the present study, we report findings of BN Rhizoctonia AG‐L, AG‐O and AG‐P, to our knowledge, for the first time in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Aiello et al (2017) found that most of AG-R, AG-A and AG-G and AG-V isolates as well as all isolates of R. solani AG 4 HG-I were pathogenic to different ornamental nurseries in Italy, but those of BN Rhizoctonia AG-Fb and R. solani AG 2 2-IIIB did not. In Turkey, however, there are no reports on the presence of BN Rhizoctonia and MN R. solani on perennial plants, but there are many reports on annual plants, including barley and wheat (Demirci, 1998), corn (Demirci & Kordali, 1999), johnsongrass (Demirci, Eken, & Zengin, 2001), legumes (Eken & Demirci, 2003), potato (Yanar, Yilmaz, Cesmeli, & Coskun, 2005), onion (Erper et al, 2006), bean (Erper et al, 2011), tabocco Gurkanlı, Ozkoc, & Gunduz, 2011), pepper (Tuncer & Eken, 2013), winter squash (Erper, Cebi Kilicoglu, Türkkan, & Onder, 2016). In the present study, we report findings of BN Rhizoctonia AG-L, AG-O and AG-P, to our knowledge, for the first time in Turkey.…”
Section: Virulence Of Rhizoctonia Isolatesmentioning
confidence: 99%